2020
DOI: 10.5114/pq.2020.95769
|View full text |Cite
|
Sign up to set email alerts
|

Effect of forward head posture on diaphragmatic excursion in subjects with non-specific chronic neck pain. A case-control study

Abstract: IntroductionForward head posture (FHP) is commonly seen in subjects with chronic neck pain (CNP) and is associated with respiratory function limitations. Therefore, the main aim of this study was to assess the effect of FHP compared with normal head posture (NHP) on diaphragmatic excursion in subjects with non-specific CNP.MethodsOverall, 30 subjects with CNP aged 35–45 years were recruited for this study and divided into 2 equal groups: the FHP group and the NHP group. The inclusion criteria were non-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Additionally, Ahmed et al compared the excursion of the diaphragm in patients with nonspeci c chronic neck pain in two groups, with FHP and with normal head posture. The results showed decreased diaphragmatic excursion in patients with nonspeci c chronic neck pain with FHP, but the difference was not statistically signi cant from the other group [55].…”
Section: Discussionmentioning
confidence: 68%
“…Additionally, Ahmed et al compared the excursion of the diaphragm in patients with nonspeci c chronic neck pain in two groups, with FHP and with normal head posture. The results showed decreased diaphragmatic excursion in patients with nonspeci c chronic neck pain with FHP, but the difference was not statistically signi cant from the other group [55].…”
Section: Discussionmentioning
confidence: 68%
“…in conclusion, whole body muscle retraining occurs and hence improves CVA. A recent study even reported a decreased diaphragmatic excursion in subjects with FHP with a non-specific chronic neck pain as compared with people with normal head posture [34].…”
Section: Discussionmentioning
confidence: 90%
“…Sixty-three studies appeared to be eligible at preliminary review, but were deemed ineligible for the following reasons: Does not independently analyze breathing/IAQ -back/neck pain relationship (N = 11) [115][116][117][118][119][120][121][122][123][124][125], duplicate data report (N = 6) [126][127][128][129][130][131], independent effects of breathing exercise that cannot be determined (N = 5) [132][133][134][135][136], missing or discrepant data that preclude interpreting eligibility or analysis (N = 7) [137][138][139][140][141][142][143], no between-group comparison for relevant outcomes (N = 6) [144][145][146][147][148][149], no comparator to analyze breathing/IAQ -back/neck pain relationship (N = 8) [150][151][152][153][154][155][156][157], no relevant therapies or outcomes (N = 18) [158]…”
Section: Figure 1: Prisma Flow Diagram Of Search Resultsmentioning
confidence: 99%